“OS INSTRUMENTOS MUSICAIS DE MOZAMBIQUE”, by Margot Dias in GEOGRAPHICA, Ano II, No. 6. April, 1966. - Kubik, Gerhard (International Library of African Music, 1966)
pages: 74-75
Keywords: African Music; Mozambique